Serum-free spontaneously immortalized bovine oviduct epithelial cell conditioned medium promotes the early development of bovine in vitro fertilized embryos - Norikazu MIYASHITA; Satoshi AKAGI; Tamas SOMFAI; Yuji HIRAO (The Society for Reproduction and Development, 2024)
Embryonic transfer of bovine blastocysts produced using in vitro fertilization (IVF) is widely used, although the challenge of compromised conception rates remains. Using bovine oviduct epithelial cells (BOEC) to improve embryo culture conditions has attracted attention, particularly since the recent discovery of extracellular vesicles from BOEC. The selection of embryos for transfer has also been the subject of various studies, and a set of evaluation criteria to predict pregnancy success has been suggested, in which the embryos are judged by their kinetics and morphology at the early stages. In the present study, we established a spontaneously immortalized BOEC line (SI-BOEC) and examined the effects of conditioned medium on IVF embryos, focusing on the results of the recommended criteria. A modified KSOM (mKSOM) was used to prepare conditioned media. Presumptive zygotes were cultured in mKSOM (control), SI-BOEC-conditioned medium, mKSOM supplemented with sediment (pellet) collected after the ultracentrifugation of the conditioned medium (mKSOM/sediment), and the supernatant. A significantly higher percentage of embryos satisfied the recommended criteria when grown in the conditioned medium than in the mKSOM. A higher proportion of embryos developed into blastocysts after achieving the four criteria. A similar tendency was observed when grown in mKSOM/sediment compared to mKSOM; however, this was not observed in the supernatant. Vesicles with a size similar to that of exosomes were observed in the sediment. In conclusion, the culture medium conditioned by SI-BOEC promoted the production of bovine blastocysts that satisfied the four evaluation criteria recommended for embryo selection.